Freedom of religion, security, and the law: key challenges for a pluralistic society - Marchei, Natascia; Milani, Daniela (Routledge-Giappichelli studies in religion, law, and economics in the Mediterranean space, 2024)
"This book was produced as part of the PriMED Project (Prevention and Interaction in the Trans-Mediterranean area), funded in Italy by the Ministry of University and Research (MUR). The title of the book, which refers to the complex relationship between the right to religious freedom and security, immediately discloses the assumptions on which the work is based. In recent decades, and particularly since September 2001, the right to religious freedom, which has always been widely protected due to its centrality in the processes of the development of the human self, has come up against a significant challenge in terms of security, or rather in the subjectively and publicly perceived feelings of insecurity. These concepts of security (here understood as public order in the substantive sense), safety and orderly civil life, are in fact being increasingly used by legal systems to limit religious freedom and are seen as an objective to which all States must aspire, even to the extent of placing restrictions on fundamental freedoms, both inside and outside the borders of Europe. The chapters reveal the importance of avoiding simplistic conclusions and unfounded prejudices about religious freedom, and of limiting restrictive or repressive interventions to situations of genuine danger"--